If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x(x + 3) = -8 Reorder the terms: x(3 + x) = -8 (3 * x + x * x) = -8 (3x + x2) = -8 Solving 3x + x2 = -8 Solving for variable 'x'. Reorder the terms: 8 + 3x + x2 = -8 + 8 Combine like terms: -8 + 8 = 0 8 + 3x + x2 = 0 Begin completing the square. Move the constant term to the right: Add '-8' to each side of the equation. 8 + 3x + -8 + x2 = 0 + -8 Reorder the terms: 8 + -8 + 3x + x2 = 0 + -8 Combine like terms: 8 + -8 = 0 0 + 3x + x2 = 0 + -8 3x + x2 = 0 + -8 Combine like terms: 0 + -8 = -8 3x + x2 = -8 The x term is 3x. Take half its coefficient (1.5). Square it (2.25) and add it to both sides. Add '2.25' to each side of the equation. 3x + 2.25 + x2 = -8 + 2.25 Reorder the terms: 2.25 + 3x + x2 = -8 + 2.25 Combine like terms: -8 + 2.25 = -5.75 2.25 + 3x + x2 = -5.75 Factor a perfect square on the left side: (x + 1.5)(x + 1.5) = -5.75 Can't calculate square root of the right side. The solution to this equation could not be determined.
| (2x^2)+5x+8=0 | | 16z=-128 | | 7-q-q-2q=80 | | 4p-25=-32+5p | | 4p-12=-3+p | | -7x-10x=-85 | | 4x-10x=70 | | -5x-15=-95 | | -60=3+9x | | (3x^2)-5x-7=0 | | (2x^2)+8x=0 | | 1+x^2=0 | | (2x^2)-7x-1=0 | | 27a^3x^4-8x=0 | | 8+2x=x+40 | | 3y+24+6-2=33 | | -28+4=0 | | ln(x+1)ln(x)+ln(x^2)=1 | | ln(x+a)ln(x)+ln(x^2)=1 | | 53-2x=5x | | 11x-10=54 | | 6p^2+25-119=0 | | (6a^3+6a^2-7)+(5a^3-6a+8)= | | 2x^2-45=0 | | y+24y+144= | | 8a+12b+4= | | 9x+12y+15= | | 6a-18b+12c= | | 12a-28b+10c= | | 40=5w-15 | | 7x-7y-7z= | | 5x-5y+10z= |